2016
DOI: 10.18632/aging.100873
|View full text |Cite
|
Sign up to set email alerts
|

Telomere attrition and restoration in the normal teleost Oryzias latipes are linked to growth rate and telomerase activity at each life stage

Abstract: Telomere shortening occurs when cells divide, both in vitro and in vivo. On the other hand, telomerase is able to maintain telomere length in cells by adding TTAGGG repeats to the ends of telomeres. However, the interrelationships existing among telomere length, telomerase activity and growth in vertebrates remain to be clarified. In the present study we measured telomere length (terminal restriction fragment length), telomerase activity and body growth of Oryzias latipes from the embryo stage until senescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 68 publications
4
43
0
Order By: Relevance
“…To our knowledge, late-growth elongation, like we observed, is only known for one species, the fish Oryzias latipes [54]. Increased telomerase activity is the proposed mechanism for developmental telomere elongation observed in O. latipes [54], so this is likely the same mechanism contributing to our results. Although we did not measure telomerase directly, we measured an increase in telomere length from shortest length on day 15 back to hatch day length by day 30, similar to what was shown in O. latipes .…”
Section: Discussionsupporting
confidence: 67%
“…To our knowledge, late-growth elongation, like we observed, is only known for one species, the fish Oryzias latipes [54]. Increased telomerase activity is the proposed mechanism for developmental telomere elongation observed in O. latipes [54], so this is likely the same mechanism contributing to our results. Although we did not measure telomerase directly, we measured an increase in telomere length from shortest length on day 15 back to hatch day length by day 30, similar to what was shown in O. latipes .…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have shown that heat stress reduced telomere length in the Siberian sturgeon Acipenser baerii (Simide, Angelier, Gaillard, & Stier, 2016) and the brown trout Salmo trutta (Debes et al, 2016). Fishes show life stage-specific telomere lengths because they exhibit lifelong somatic growth and express telomerase across tissues and throughout all life stages (Anchelin, Murcia, Alcaraz-Pérez, García-Navarro, & Cayuela, 2011;Hartmann et al, 2009;Hatakeyama et al, 2016). Fishes show life stage-specific telomere lengths because they exhibit lifelong somatic growth and express telomerase across tissues and throughout all life stages (Anchelin, Murcia, Alcaraz-Pérez, García-Navarro, & Cayuela, 2011;Hartmann et al, 2009;Hatakeyama et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…by up‐regulation of oxidative defence mechanisms; von Zglinicki et al ., ), or restore telomeres (e.g. by increasing telomerase activity; Hatakeyama et al ., ), would be an active process, and thus by definition require energy and be involved in trade‐offs with other energy‐demanding processes, like growth.…”
Section: Discussionmentioning
confidence: 99%